Indywidualne gospodarstwa rolne w ustroju społeczno-gospodarczym PRL (rozważania na tle art. 131 k.c.) - Budzinowski, Roman (Wydział Prawa i Administracji UAM, 1983)
A new regulation of sec. 131 of the Civil Code (cc.) is deserving particular attention in the aspect of defining a place and role of indvidual farms in the socio-economic system. It is a new substantiation of a general clause of interpretation and application of civil law provisions formulated in sec. 4 c.c. In its impact the regulation exceeds a role of the interpretational directive. It is the most exhaustive, in our legislation, formulation of a relation of the State to individual farms. Two question's are the subject off detailed discussions i.e.: a) individual farms as a stable and equal in rights element of the socio-economic system, b) guarantees of ownership and complete protection of individual farms. There is an apparent interrelation between the- guarantees of ownership and complete protection afforded by the State to individual farmls, and recognizing these farm's as a stable and equal in rights element of the socio-economic system. Yet, the guarantees of ownership and complete protection do not preempt the State's right of intervention. It seems justified to say that the ownership of individual farms is guaranteed by the State in certain limits and under certain conditioms. The regulation of sec 131 c.c, will be expressing current trends in the legislation determined by political considerations, until it is reflected in the Constitution. The article is concluded with the postulates on the developement of agrarian policies, on legislation and on the studies on agricultural law.
Individual farms in the socio-economic system of Poland (a study on sec. 131 of the Polish Civil Code)